2022
DOI: 10.11606/s1518-8787.2022056003672
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade por doença respiratória crônica no Brasil: tendência temporal e projeções

Abstract: OBJETIVO Analisar a tendência temporal das taxas mensais de mortalidade por doenças respiratórias crônicas no Brasil de 1996 até 2017, com projeções para 2022, além de analisar a possibilidade de cumprimento da meta do Plano de Ações Estratégicas para o Enfrentamento das Doenças Crônicas Não Transmissíveis no Brasil de 2011 até 2022. MÉTODOS Trata-se de estudo ecológico que utiliza dados do Sistema de Informações sobre Mortalidade, do Sistema de Informações Demográficas e Socioeconômicas e da Pesquisa Nacional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 17 publications
(18 reference statements)
1
13
0
2
Order By: Relevance
“…Most hospitalisations caused by RD from 2008 to 2021 were due to pneumonia, corroborating with Zhao et al , who also showed pneumonia as the main cause of hospitalisations in both sexes in the last 16 years 21. However, the overall hospitalisations reduced from 2008 to 2021 (26.32%), suggesting improved health promotion, surveillance and comprehensive care, especially with actions for smoking cessation and improved access to health services and medications 6. Studies have shown that the prevalence of smokers in Brazil in 1989 was 34.8% in those aged 18 years or more.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Most hospitalisations caused by RD from 2008 to 2021 were due to pneumonia, corroborating with Zhao et al , who also showed pneumonia as the main cause of hospitalisations in both sexes in the last 16 years 21. However, the overall hospitalisations reduced from 2008 to 2021 (26.32%), suggesting improved health promotion, surveillance and comprehensive care, especially with actions for smoking cessation and improved access to health services and medications 6. Studies have shown that the prevalence of smokers in Brazil in 1989 was 34.8% in those aged 18 years or more.…”
Section: Discussionsupporting
confidence: 80%
“…Also, the reduced hospitalisation rate in all regions from 2008 to 2021 may be related to the beginning of influenza vaccination (1999), even considering the different causes of respiratory infections 25. In addition, this result may occur due to improved health conditions and access to health services 6…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations